Shifting frontal regimes and its influence on bioproductivity variations during the Late Quaternary in the Indian sector of Southern Ocean. (August 2015) - Manoj, M.C.; Thamban, Meloth
Abstract: Reconstruction of palaeoproductivity from Southern Ocean is crucial for understanding the functioning of the Southern Ocean biological pump in the past. High resolution records of multi-proxy parameters (calcium carbonate, opal, total organic carbon biogenic barium and planktonic carbon isotope ratios (δ 13 C)) were investigated in two well-dated sediment cores (SK200/22a and SK200/27) from the Indian sector of Southern Ocean situated to the north and south of Antarctic Polar front (APF), respectively. The palaeoproductivity records extending 95 ka BP (SK200/22a) and 75 ka BP (SK200/27) revealed inverse relationships between the calcite and opal productivity, indicating the influence of shifting nutrient regimes. At core SK200/22a, reduced calcite productivity during marine isotope stage (MIS) 2, 4, and part of MIS 3 suggest an equatorward migration of the frontal regimes during glacial intervals. Compared to this, the region south of the APF (core SK200/27) was characterized by the near absence of calcite content during the last glacial period and increased opal productivity during MIS 1 and MIS 3, supporting a southward migration of APF during warmer intervals. Ba(bio) records exhibit good correlation with opal records in both the cores and also correlate with that of calcite record at SK200/22a, indicating that Ba is influenced by the combined opal and calcite productivity. The enhanced opal productivity during the glacial periods north of the APF is attributed to the northward shifting of oceanic fronts and associated transfer of nutrients. Diatom productivity records of SK200/22a reveal significant similarities with the dust records from the Antarctic and Southern Ocean, but showed no significant relationships with the diatom record of SK200/27. It is proposed that the dust-derived Fe input had apparently influenced the palaeoproductivity north of the modern APF, but had a minor influence on opal productivity south of the APF. Comparison with the ice core climate records from Antarctica and Greenland revealed that bioproductivity peaks in the study region are nearly synchronous with the millennial Antarctic warming events. Remarkably, the calcite and opal productivity records at SK200/22a responded differently to the Antarctic warming events, with opal productivity lagging behind the calcite productivity peaks by 1–2 ka.